Acrocarpus fraxinifolius Wight and Arn. Bark; phenolics, toxicity studies, antioxidant and anti-inflammatory activities (Brazilian Journal of Pharmaceutical Sciences, 2022)
The purpose of the survey was to determine acute & chronic toxicity; in vivo antioxidant and anti-inflammatory actions of the different extracts of A. fraxinifolius Wight and Arn bark; along with estimation of the phenolic, flavonoidal contents and investigation of phenolic metabolites that may attribute to the activities. LD50 of the total ethanol extract (TEE) was 7.1 g/kg b. wt, the radical scavenging activity of DPPH showed 60.31% inhibition, FRAP ability and ABTS+ activity showed 55.024 and 67.217 µmol Trolox/100 g dry weight, respectively. TEE followed by ethyl acetate extract (EAE) at 100 mg/kg b.w exhibited the highest in vivo antioxidant activity (94.51% and 91.08% potency, respectively) compared with Vit E (100%). The TEE & EAE exhibited the highest anti-inflammatory activity (3.81±0.08 & 3.79±.0.04) respectively in comparison with indomethacin 3.83±0.01 measured as edema diameter after 4 hours of extract administration. The total phenolic and total flavonoid contents in the total ethanol extract (TEE) estimated as gallic acid and catechin equivalents were 61.06± 0.08 μg eq GA/g, 40.33± 0.20 μg CE/g extract respectively. EAE revealed five phenolic acids and eight flavonoid compounds isolated for the first time from the plant.